Glycine tabacina ethanol extract ameliorates collagen-induced arthritis in rats via inhibiting pro-inflammatory cytokines and oxidation. (12th June 2019) - Tu, Yanbei; Wang, Kai; Liang, Yeer; Jia, Xuejing; Wang, Lili; Wan, Jian-Bo; Han, Jianping; He, Chengwei
Abstract: Ethnopharmacological relevance: The whole plant of Glycine tabacina (Labill.) Benth has been used as a traditional herbal medicine to treat rheumatism, ostealgia and nephritis in China. It is also one of the sources of the renowned native herbal medicine 'I-Tiao-Gung' in Taiwan. Aim of the study: This study aimed to investigate the anti-arthritic effect of ethanol extract of G. tabacina (GTE) in a collagen-induced arthritis (CIA) rat model. Materials and methods: The chemical profile of GTE was analyzed by HPLC-UV. The CIA was induced in male Wistar rats by intradermal injection of bovine type II collagen at tail root, back and ankle joints. The rats were orally administrated daily with GTE (1.11, 2.22 and 4.44 g dry weight of herb powder per kg body weight) from day 0 and continued for 30 days. Swelling volume and thickness of paw, arthritis index, X-radiographs and histopathological changes were examined to assess the severity of arthritis. Furthermore, the levels of pro-inflammatory cytokines, such as interleukin1β (IL-1β), IL-6 and tumor necrosis factor α (TNF-α), total superoxide dismutase (T-SOD) activity and malonaldehyde (MDA) level were measured to preliminarily explore the possible mechanisms. Results: Oral administration of GTE significantly ameliorated the arthritic symptoms in CIA rat model, as indicated by the effects on paws swelling and arthritis index. X-radiographic analysis and histopathological examinations demonstrated that GTE effectively protected the bone and cartilage of joints from erosion, lesion and deformation. The efficacy of GTE treatment on CIA was comparable to that of indomethacin (positive drug). Besides, the overproduction of IL-1β, IL-6 and TNF-α was remarkably inhibited in the serum of all GTE treatment groups. The restoration of serum T-SOD activity and MDA level proved that GTE administration alleviated the oxidative stress in CIA rats. Conclusions: GTE exhibited strong anti-CIA activity through inhibiting pro-inflammatory cytokines and oxidation in rats, suggesting its potential preventive and therapeutic effects on rheumatoid arthritis (RA). Graphical abstract: Image 1